The Influence of Price, Promotion, and Digital Lifestyle on Online Shopping Frequency on E-Commerce Platforms (Case Study on Gen Z Students of the Faculty of Economics at Universitas Merdeka Madiun) - Deva Satya Pradana; Muhammad Imron; Hartirini Warnaningtyas (Citakonsultindo, 2026)
The rapid development of information and communication technology has increased the use of e-commerce platforms for online shopping activities. Generation Z is a group with a high level of technological adaptation, making online shopping an integral part of their daily lives. This study aims to analyze the influence of price, promotion, and digital lifestyle on the online shopping frequency of Generation Z students at the Faculty of Economics, Universitas Merdeka Madiun. This research employed a quantitative method with a causal associative approach. The sample consisted of 133 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The results indicate that price has a positive and significant effect on online shopping frequency (t = 4.794; sig. = 0.000). Promotion also has a positive and significant effect on online shopping frequency (t = 3.943; sig. = 0.000). In contrast, digital lifestyle does not have a significant effect on online shopping frequency (t = 1.219; sig. = 0.225). Simultaneously, price, promotion, and digital lifestyle significantly influence online shopping frequency (F = 92.157; sig. = 0.000). The Adjusted R Square value of 0.674 indicates that 67.4% of the variation in online shopping frequency can be explained by the three independent variables. The study concludes that price and promotion are significant factors influencing online shopping frequency, while digital lifestyle does not have a significant partial effect. Price is the most dominant factor affecting students’ online shopping frequency.